Reading Republican oratory reconstructions, contexts, receptions - Gray, Christa 1982-; Balbo, Andrea 1970-; Marshall, Richard M. A. 1983-; Steel, Catherine E. W. 1973- (Oxford University Press, 2018)
Public speech was a key aspect of politics in Republican Rome, yet the partial nature of the available evidence means that our understanding of its workings is dominated by one man: Cicero. This volume explores the oratory of the Roman Republic as practiced by individuals other than Cicero, focusing on the surviving fragments of such oratory